2019
DOI: 10.1002/mrm.27668
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood volume mapping using Fourier‐transform–based velocity‐selective saturation pulse trains

Abstract: Purpose Velocity‐selective saturation (VSS) pulse trains provide a viable alternative to the spatially selective methods for measuring cerebral blood volume (CBV) by reducing the sensitivity to arterial transit time. This study is to compare the Fourier‐transform–based velocity‐selective saturation (FT‐VSS) pulse trains with the conventional flow‐dephasing VSS techniques for CBV quantification. Methods The proposed FT‐VSS label and control modules were compared with VSS pulse trains utilizing double refocused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 47 publications
0
64
0
Order By: Relevance
“…Velocity selective arterial spin labeling (VS-ASL) is a promising technique for transit time insensitive, non-contrast perfusion and vascular imaging. [6][7][8] VS-ASL has been used to demonstrate post labeling delay insensitive visualization of cerebral blood flow (CBF) in cases of delayed filling 9,10 and has also been used to demonstrate agreement with 15 O-PETbased measures of CBF. 11 Although no defined tagging plane is required, VS-ASL tagging is still subject to other error sources that can result in global or regional changes in tagging efficiency including eddy currents, cardiac cycle-dependent flow, velocity directionality, and heterogeneity of B 0 and B 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Velocity selective arterial spin labeling (VS-ASL) is a promising technique for transit time insensitive, non-contrast perfusion and vascular imaging. [6][7][8] VS-ASL has been used to demonstrate post labeling delay insensitive visualization of cerebral blood flow (CBF) in cases of delayed filling 9,10 and has also been used to demonstrate agreement with 15 O-PETbased measures of CBF. 11 Although no defined tagging plane is required, VS-ASL tagging is still subject to other error sources that can result in global or regional changes in tagging efficiency including eddy currents, cardiac cycle-dependent flow, velocity directionality, and heterogeneity of B 0 and B 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In that paper, block pulses were recommended over composite pulses for refocusing, due to the adequate immunity of Mz‐velocity response to B 0 /B 1 field inhomogeneities with shorter pulse durations and less SAR constraints. For VSASL, when only correct B1+ scales were evaluated with respect to gradient imperfections, block refocusing pulses were shown sufficient to suppress false signal from static tissue 21,24 . In this current work, when poor B 1 conditions were examined as large spatial coverage would incur, simulations of Mz‐position responses (Figure 2), as well as phantom (Figure 3) and human (Supporting Information Figure ) results all demonstrated that composite refocusing pulses were more robust over block refocusing to minimize both eddy‐current and B 1 related artifacts.…”
Section: Discussionmentioning
confidence: 64%
“…For VSASL, when only correct B + 1 scales were evaluated with respect to gradient imperfections, block refocusing pulses were shown sufficient to suppress false signal from static tissue. 21,24 In this current work, when poor B 1 conditions were examined as large spatial coverage would incur, simulations of Mzposition responses (Figure 2), as well as phantom ( Figure 3) and human (Supporting Information Figure S2) results all demonstrated that composite refocusing pulses were more robust over block refocusing to minimize both eddy-current and B 1 related artifacts. The erroneous phases from eddy-currents associated with gradient lobes surrounding the refocusing pulses might be better canceled, when B 1 is with correct setting (middle column of Figures 2 and 3), or refocusing pulses are less sensitive to B 1 offset (second row of Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…However, with the 2 cm/s cutoff velocity used here, the b‐values for label and control were 0.5 and 0.0 s/mm 2 with scheme 1 and 3, versus 0.5 and 0.2 s/mm 2 with scheme 2. While this effect was negligible in this VSASL study, it remains an issue in the measurement of blood volume using velocity‐selective pulse trains, 20,21 by which much lower cutoff velocity is pursued. It is also worth emphasizing that, although the dynamic phase‐cycling removes subtraction errors of static spins and preserves the velocity‐selective profiles, the labeling efficiency is still scaled by incorrect B1+ setting (Figure 1A) because the inversion degree is determined by the flip angles of the hard pulses used at the beginning of each velocity‐encoding step 8 .…”
Section: Discussionmentioning
confidence: 87%